O produto das raízes da equação é:
Anexos:
![](https://pt-static.z-dn.net/files/d74/2a37e4be3075a42d2cc69e74963357ef.jpeg)
Soluções para a tarefa
Respondido por
1
Boa tarde
9^x - 10*3^x + 9 = 0
y = 3^x
y² - 10y + 9 = 0
(y - 1)*(y - 9) = 0
y1 = 1, x1 = 0
y2 = 9 , x2 = 2
produto P = 0
9^x - 10*3^x + 9 = 0
y = 3^x
y² - 10y + 9 = 0
(y - 1)*(y - 9) = 0
y1 = 1, x1 = 0
y2 = 9 , x2 = 2
produto P = 0
Perguntas interessantes
Artes,
11 meses atrás
História,
11 meses atrás
Filosofia,
11 meses atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás